KNOWLEDGE MANAGEMENT PRACTICES IN INDIAN SOFTWARE DEVELOPMENT COMPANIES: FINDINGS FROM AN EXPLORATORY STUDY - Manish Kumar,; Souren Paul,; Suresh Tadisina, (Asian Academy of Management Journal, 2005)
Knowledge management (KM) is becoming an important management responsibility as organizations increasingly invest significant information technology (IT) resources to support acquisition, storage, sharing, and retrieval of knowledge. Furthermore, KM plays a critical role in organizations that rely primarily on intellectual capital, such as software development companies. In this paper, we report the findings of an exploratory study where we investigate the KM practices of eight leading software consultancy companies in India and compare our findings with results from a similar study by Alavi and Leidner (1999). Finally, we suggest a technical and social infrastructure to help enhance KM capability of software development companies in India.